2010
DOI: 10.1021/nn9017872
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin Adsorption, Cell Adhesion, and Proliferation on Nanostructured Tantalum Surfaces

Abstract: The interaction between dental pulp derived mesenchymal stem cells (DP-MSCs) and three different tantalum nanotopographies with and without a fibronectin coating is examined: sputter-coated tantalum surfaces with low surface roughness <0.2 nm, hut-nanostructured surfaces with a height of 2.9 +/- 0.6 nm and a width of 35 +/- 8 nm, and dome structures with a height of 13 +/- 2 nm and a width of 52 +/- 14 nm. Using ellipsometry, the adsorption and the availability of fibronectin cell-binding domains on the tantal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
132
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(138 citation statements)
references
References 65 publications
6
132
0
Order By: Relevance
“…22 The formation of focal adhesion contacts and cell adhesion is an important starting point for cell proliferation, differentiation, and some cellular behaviors, which is activated by the formation of vinculin adhesion spots. 23,24 The higher expression exhibited better adhesion. It has been reported that various kinds of physical stresses can accelerate stem cell differentiation into specific cells.…”
mentioning
confidence: 99%
“…22 The formation of focal adhesion contacts and cell adhesion is an important starting point for cell proliferation, differentiation, and some cellular behaviors, which is activated by the formation of vinculin adhesion spots. 23,24 The higher expression exhibited better adhesion. It has been reported that various kinds of physical stresses can accelerate stem cell differentiation into specific cells.…”
mentioning
confidence: 99%
“…A typical review, focusing on 2D nanotopographical surfaces, highlighted that cells are in some cases essentially controlled by the surface-adsorbed proteins rather than by direct signaling from nanoscale surface cues. 23 However, recent studies found that the adsorbed fibronectin did not affect cell adhesion on nano-hut/dome tantalum surfaces compared to flat surfaces, 14 and the reduced cell adhesion on TiC nanowires 18 and SiO 2 nanorods 19 was independent of protein adsorption. These findings imply that the process of cell adhesion on 3D nanotopographs may be directly mediated by signaling from nanoscale surface cues rather than by surface-adsorbed proteins, although there was lack of evidence in the absence of serum.…”
Section: Introductionmentioning
confidence: 95%
“…8 Cell-material interactions depend on the surface properties of the material, such as chemistry, 2,9-11 surface energy, 2,12 roughness, 13 and topography. [14][15][16][17][18][19][20][21][22] Recent works demonstrated that three-dimensional (3D) nanotopography could influence cell adhesion; however, conflicting results have been reported. For example, hydroxyapatite (HA) nanoneedles and nanofibers, 17 quasi-aligned TiC and TiO 2 nanowires, 18 and randomly oriented and upright SiO 2 and ZnO nanorods 19 inhibited adhesion and spreading of cells.…”
Section: Introductionmentioning
confidence: 99%
“…It was documented that the surface fibronectin adsorption is directly related to cell functions. 29 Moreover, our plasma Ti-coated samples required no chemical etchants or subsequent postprocessing. The treatment method uses a Ti plasma to modify the surface, thereby eliminating the possibility of metal contaminants.…”
Section: Plasma Nanocoating For Improved Stem Cell Functionsmentioning
confidence: 99%